1.3 kW Continuous Wave Output Power of Ytterbium-Doped Large-Core Fiber Laser. (24th February 2021) - Sohail, Muhammad; Khan, Noor Zamin; Chen, Tenghui; Ullah, Asmat; Ahmed, Jahangeer; Alshehri, Saad M.; Ahmad, Faisal; Ali Khan, Sayed
Abstract : A very efficient key cladding-pumped trivalent ytterbium (Yb 3+ ) doped fiber laser has been developed. The whole fiber laser system generated 1.3 kW of continuous-wave (CW) maximum output power with very high efficiency at 1.1 μ m and near the diffraction beam quality (M 2 = 1.27). The measure slop efficiency is 76% and shows no limit of temperature and nonlinear effects. In a preliminary proof of principle study, efficient single-mode operation of a cladding-pumped ytterbium-doped fiber laser with a diameter core and a numerical aperture of 0.09 has been demonstrated. When pumped to the ends of both fibers, they have strong beam quality and display no signs of rolling over even at the highest output power. The large core ytterbium doped fiber laser (YDFL's) is end pumped with diodes stack source through opposite ends of fiber. This design of fiber can delivers maximum output power which is restricted mostly by accessible pump power.